Bubbles of Landau-Lifshitz Equations with Applied Fields (Journal of Partial Differential Equations, 2005)
In this paper, we discuss the Landau-Lifshitz equations with applied magnetic fields. The equations describing the bubbles in the ferromagnets and the behaviors of the solutions near the singularities are given. We found that the applied fields do not affect the bubbles and we have the same conclusions as in reference [1].
Keywords: Landau-Lifshitz equations; magnetic fields; bubbles